Anthropoetics as a super-system approach to the study of public health - Biryukov, Viktor; Gozhenko, Anatolii; Zukow, Walery (Journal of Education, Health and Sport, 2025)
Background: Health as a biosocial phenomenon is studied across multiple scientific disciplines, yet increasing specialization has resulted in fragmented knowledge and a loss of holistic perspective. Contemporary global challenges - including climate change, pandemics, and artificial intelligence - demand a new integrative ethical framework. Objective: This article introduces anthropoetics as a super-system approach to public health, aiming to unify existing ethical systems (bioethics, technoethics, noetics) into a comprehensive paradigm addressing modern civilizational risks. Methods: The study employs: Bioethical and systems theory analysis (ISO 9001:2015 standards). Ontological modeling (STCHH - space-time continuum of human health). Historical-dialectical review of ethical systems evolution Results: Anthropoetics emerges as an ethical super-system based on four pillars: Interconnectedness of all life and cosmic elements. Sustainable development principles. Consciousness as a foundation for ethical norms. Humanism respecting all life forms Conclusions: Anthropoetics provides a transformative paradigm for public health research and policy, requiring international collaboration for implementation. Its super-system structure offers novel solutions for harmonizing scientific progress with ethical imperatives in the Anthropocene era.